Pregnancy after Breast Cancer: State of the Art - Guedes, Helena (2017)
Breast cancer survivors have given rise to several issues of major relevance from a clinical and scientific point of view. In fact, breast cancer is the most prevalent malignancy in women of reproductive age. The effect of pregnancy on overall survival and in the recurrence after treatment of breast cancer, as well as the questions related to heredity continue to be matter of the highest timeliness and scientific interest. Most recent studies seem to agree in admitting that pregnancy after breast cancer appears to be potentially safe to both the women and her offspring, although this issue remains complex. Heredity and genetics seem to play an important role in this subject, but the conclusions lack absolute and unequivocal consistency. There is a need for meta-analysis, cohort and case-control studies, translational and prospective studies extended in time, in order to obtain greater safety in the establishment of strategies and guidelines for clinicians and adequate objective information for young breast cancer patients.